DEVELOPMENT OF CHEMSITRY TEACHER PROFESSIONALISM THROUGH PEDAGOGICAL CONTENT KNOWLEDGE TRAINING - Haryani, Sri; Wardani, Sri; Prasetya, Agung Tri (Universitas Negeri Semarang, 2016)
This study aims to analyze the impact of Pedagogical Content Knowledge (PCK) training to the development of chemistry teachers’ professionalism through MGMP. The study involved 5 chemistry teachers who measured the PCK capability through filling CoRe (Content Representation) and writing PaPeRs (Pedagogical and Professional-experience Repertoires), which represents the PCK of a teacher as proposed by Loughran. Quantitative data drawn from the results of the fillingCoRe,Lesson Plan (RPP), and PaP-eRs instruments, whereas qualitative data were taken from the three linkage analysis supported by the results of the interview. Based on the results of data analysis revealed that PCK training can develop the teachers professionalism as measured by the PCK capability especially in minimizing the weaknesses that have been prevalent as how to express apperception, the depth of the material, determine the learning strategies, and pay attention to the prerequisites material.